Influence of running-in operating conditions on the steady-state torque loss of ground spur gears - Carlos M C G Fernandes (2021)
The influence of gear running-in operating conditions on the steady-state efficiency of ground spur gears is not well established. However, it is accepted that less rough surfaces promote better efficiency. Five ground spur gears with similar surface finishing were submitted to two distinct test stages: (i) running-in stage and (ii) torque loss stage. During the running-in stage, five different running-in operating conditions were conducted to ascertain the influence of the load and temperature on the subsequent steady-state gear torque loss test. The mass loss and surface roughness parameters were influenced by the running-in operating conditions. However, different surface conditions after running-in had only a transient effect on the torque loss measured subsequently. So, the test campaign allow to conclude that even after a severe running-in operating condition, the gears surface still evolves in a significant way during the torque loss tests.